Gender differences in business performance: evidence from the characteristics of business owners survey - Robert W. Fairlie; Alicia M. Robb (Institute for the Study of Labor (IZA), 2008)
Using confidential microdata from the U.S. Census Bureau, we investigate the performance of female-owned businesses making comparisons to male-owned businesses. Using regression estimates and a decomposition technique, we explore the role that human capital, especially through prior work experience, and financial capital play in contributing to why female-owned businesses have lower survival rates, profits, employment and sales. We find that female-owned businesses are less successful than male-owned businesses because they have less startup capital, and business human capital acquired through prior work experience in a similar business and prior work experience in family business. We also find some evidence that female-owned businesses work fewer hours and may have different preferences for the goals of their business.
urn:nbn:de:101:1-20081014177
Keywords: J15; 330; Female entrepreneurship; business outcomes; Weibliche Führungskräfte; Unternehmer; Unternehmensentwicklung; Berufserfahrung; Risikokapital; Vergleich; Männer; USA